The «death of God» in Nietzsche again. The «death of God» as a transversal category of nietzschean vitalist Philosophy - Casadesús, Ricard (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
We could call Nietzsche a heroic and innovative prophet, who makes an oracle of decadence, denouncing the triumph of the suprasensible, the ideal, the imposition of another world as the story of an error, of an illusion, common source of all the fictions, prejudices and dogmatisms of the western cultural tradition. However, the thought that Nietzsche expresses with the death of God, and that entails the end of Christianity and metaphysics, has a metaphysical origin and a genuinely Christian origin.
Keywords: Nietzsche; vitalism; death of God; anti-platonism